Metal dusting of nickel-based alloys - GRABKE, H. J; MÜLLER-LORENZ, E. M; KLÖWER, J; AGARWAL, D. C (Materials performance, 1998)
The carburization behavior of nine commercial nickel-based alloys and four iron-nickel-chromium alloys was investigated at 650 deg C in a carburizing carbon monoxide (CO)-H sub 2 hydrogen oxide (H sub 2O) gas with a carbon activity (a sub c) of a sub c > > 1. The Fe-Ni-Cr alloys suffered severe metal dusting after a very short test period. Nickel-based alloys were generally less susceptible to metal dusting than Fe-based alloys. Nickel-based alloys with Cr concentrations of 25% and above, on the other hand, showed no significant evidence of metal dusting even after 10 # 000 # h of exposure. It was found that these alloys were protected against metal dusting by the formation of a dense, self-healing chromia scale, which prevented the penetration of carbon into the base metal. Material includes N06601 nickel base alloy.